2012
DOI: 10.1007/s00467-012-2156-2
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 and interleukin-8 levels in the urine of children with renal scarring

Abstract: Further experimental studies are required to demonstrate the correlation between histopathology and urinary cytokine levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 24 publications
1
30
0
Order By: Relevance
“…It may have influenced the levels of cytokines. Tramma turned his attention to the method of cytokine measurement in various studies [40]. Some investigators indicated that age and gender of a child may influence the cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…It may have influenced the levels of cytokines. Tramma turned his attention to the method of cytokine measurement in various studies [40]. Some investigators indicated that age and gender of a child may influence the cytokine levels.…”
Section: Discussionmentioning
confidence: 99%
“…In the kidney, tubular epithelial cells and podocytes produce these interleukins as part of an inflammatory response following most types of injury, including ischaemia–reperfusion injury and pyelonephritis 8992 . The potential utility of IL-6 and IL-8 as in vivo biomarkers of AKI is unclear, but a pilot study that assessed the effects of gentamicin and cadmium chloride on primary proximal tubule cells from two different donors showed greater upregulation of IL-6 and IL-8 than KIM1 levels in response to the compounds 82 .…”
Section: Characterization Of Cellular Modelsmentioning
confidence: 99%
“…Recently, it has been demonstrated that local and systemic levels of IL8 are increased in cicatrizing inflammatory conditions such as autoimmune glomerulonephritis (Tramma et al. ), Stevens–Johnson syndrome (SJS) (Gurumurthy et al. ), toxic epidermal necrolysis (TEN) (Paquet et al.…”
Section: Introductionmentioning
confidence: 99%
“…Several evidence demonstrated that ocular surface scarring occurring in ocular MMP is the result of the inflammatory response and the release of fibrogenic cytokines and mediators by inflammatory cells and fibroblasts which induce conjunctival fibrosis and extracellular matrix deposition (Razzaque et al 2001(Razzaque et al , 2003Dart 2017). Recently, it has been demonstrated that local and systemic levels of IL8 are increased in cicatrizing inflammatory conditions such as autoimmune glomerulonephritis (Tramma et al 2012), Stevens-Johnson syndrome (SJS) (Gurumurthy et al 2018), toxic epidermal necrolysis (TEN) (Paquet et al 2007) and idiopathic pulmonary fibrosis (Southcott et al 1995). It has been showed that IL8 plays a key role in stimulating fibrogenic inflammatory reaction through neutrophils recruitment (Murphy 1997;Yang et al 2018).…”
Section: Introductionmentioning
confidence: 99%